2020
DOI: 10.1038/s41419-020-2367-6
|View full text |Cite
|
Sign up to set email alerts
|

MMP9 mediates acute hyperglycemia-induced human cardiac stem cell death by upregulating apoptosis and pyroptosis in vitro

Abstract: Providing a conducive microenvironment is critical to increase survival of transplanted stem cells in regenerative therapy. Hyperglycemia promotes stem cell death impairing cardiac regeneration in the diabetic heart. Understanding the molecular mechanisms of high glucose-induced stem cell death is important for improving cardiac regeneration in diabetic patients. Matrix metalloproteinase-9 (MMP9), a collagenase, is upregulated in the diabetic heart, and ablation of MMP9 decreases infarct size in the non-diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 42 publications
3
48
0
1
Order By: Relevance
“…It was recently shown that the role of MMP-9 in hyperglycemia-induced cell death in human cardiac stem cells showed MMP-9 initiates apoptosis irrespective of hyperglycemia and determines MMP-9 upstream to SAPK/JNK signaling and demonstrated MMP-9-mediated apoptosis. This study also reveals that MMP-9 is upstream to MAP/JNK signaling and plays a major role in hyperglycemia-induced ROS generation in human cardiac stem cells (Yadav et al 2020). Briefly, MMP-9 has a pivotal role in cell survival.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…It was recently shown that the role of MMP-9 in hyperglycemia-induced cell death in human cardiac stem cells showed MMP-9 initiates apoptosis irrespective of hyperglycemia and determines MMP-9 upstream to SAPK/JNK signaling and demonstrated MMP-9-mediated apoptosis. This study also reveals that MMP-9 is upstream to MAP/JNK signaling and plays a major role in hyperglycemia-induced ROS generation in human cardiac stem cells (Yadav et al 2020). Briefly, MMP-9 has a pivotal role in cell survival.…”
Section: Discussionmentioning
confidence: 55%
“…MTT assay was employed to measure the toxicity in cancer and healthy cells caused by nanoparticle's exposure to find the lethal toxic dose. Also, toxicity in cells caused by nanoparticles was further assessed for the Apoptotic pathway and the regulation of metalloprotease enzymes, which are crucial in the cell death pathway (Kessenbrock et al 2010;Yadav et al 2020). The possible mechanism of toxicity lead by Ag-NP or Cu-NP is mainly by oxidative stress, DNA damage and lipid peroxidation, involving apoptosis or autophagy cell death pathway.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the role of MMP9 in epigenetic modifications in hCSCs, we created and validated MMP9 knockout (MMP9KO) hCSCs by CRISPR-Cas9 method 18 ( Figure S1A-D). To determine whether MMP9 mediates epigenetic modifications, we measured protein levels of canonical DNMT1 and DNMT3a in the control and MMP9KO hCSCs.…”
Section: Resultsmentioning
confidence: 99%
“…However, the activity of MMP9 was higher in the HG medium ( Figure S1E), which was consistent with our previous report. 18 We supplemented MMP9 by adding HG or NG culture medium to the MMP9KO hCSCs for 24 hours. To determine the paracrine effects of MMP9 on epigenetic modifications and autophagy in the MMP9KO hCSCs, we compared the levels of DNMT3a, H3K9me1, H3K9me2 HDAC1, SIRT1, LC3BII, and p62 in untreated MMP9KO hCSCs to the HG-medium treated MMP9KO and control hCSCs.…”
Section: Histone Deacetylation Causes Chromatin Condensation Andmentioning
confidence: 99%
See 1 more Smart Citation